2019
DOI: 10.1123/jsr.2017-0219
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effects of the Kinesio Taping® on Early Postoperative Hip Muscle Weakness in Male Patients With Hamstring Autograft or Allograft Anterior Cruciate Ligament Reconstruction

Abstract: ACLR-HSD can be caused by postoperative increased swelling and reduced knee strength. The KT treatment with lymphatic correction and muscle facilitation that can be used in treatment of postoperative hip muscle weakness after ACLR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 13 publications
0
12
0
1
Order By: Relevance
“…Six studies93–98 investigated the effectiveness of kinesio-tape application compared with no kinesio-tape or sham application in rehabilitation after ACL surgery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six studies93–98 investigated the effectiveness of kinesio-tape application compared with no kinesio-tape or sham application in rehabilitation after ACL surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies [93][94][95][96][97][98] investigated the effectiveness of kinesio-tape application compared with no kinesio-tape or sham application in rehabilitation after ACL surgery. Summary ► There are contradictory results on the effectiveness of kinesio-tape application on pain, swelling, range of motion and quadriceps strength.…”
Section: Kinesio-tapingmentioning
confidence: 99%
“…The peak MVC torque was recorded and normalized for body mass. In addition, isometric and concentric hamstring-to-quadriceps (H:Q) ratios as an indicator of knee joint stability [18], and symmetry values of the knee flexion and extension strength (limb symmetry index = right leg/ left leg * 100) [19] were calculated.…”
Section: Measurementsmentioning
confidence: 99%
“…Kinesiotaping (KT) has gained popularity in clinical practice worldwide as a promising method for treatment in musculoskeletal rehabilitation (3). It has been suggested that the benefits of KT arise through increased stimulation of mechanoreceptors and increased interstitial space (20).…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence of improved perceived functions of the affected knee joint (5,27), gait pattern (5), balance (27,32), and enhanced proprioception (5,27) after short-term application of KT (#3 hours) in individuals with surgically untreated ACL ruptures. In addition, there is evidence of improved muscle strength (after 10 days of KT application after ACL reconstruction) (3,4). Thus, long-term kinesiology tape application can be expected to improve proprioception and motor function in such cases.…”
Section: Introductionmentioning
confidence: 99%